(3GdEfLjds ((3ehSj GdeYQha JdejP CfHG dhbG GdSGFM s)
(3ChdgG (B:s
(3fHOC HGSe QHfG jShY GdeSjM s
(3BNQgG (B:s
(3ai GdUfOhb GdebOS JeJ CjGe GdSfI CYjGO GdbOjSjf Gddg jQMefG HUdGJge s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B175s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcJH GdSeGhjIs